Heat and Learning - Joshua S. Goodman; Michael Hurwitz; Jisung Park; Jonathan Smith (Center for Economic Studies and ifo Institute (CESifo), 2018)
We demonstrate that heat inhibits learning and that school air-conditioning mitigates this effect. Student fixed effects models using 10 million PSAT-retakers show hotter school days in years before the test reduce scores, with extreme heat being particularly damaging. Weekend and summer heat has little impact, suggesting heat directly disrupts learning time. New nationwide measures of school air-conditioning imply such infrastructure largely offsets heats effects and passes simple benefit-cost tests. Without air-conditioning, a 1°F hotter school year reduces that years learning by one percent. Hot school days disproportionately impact minority students, accounting for roughly five percent of the racial achievement gap.
Keywords: I20; 330; heat; climate; learning; air conditioning